Lithium ion battery, preparation method thereof and detection method of cycle performance of battery
By meeting specific porosity and thickness formulas on lithium-ion batteries, the problem of inconsistent electrolyte throughput during cyclic charging and discharging of lithium-ion batteries is solved, which improves cyclic performance and simplifies cyclic detection.
Patent Information
- Application Number
- CN202411369040.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-31
AI Technical Summary
During the cycle charging and discharging process of lithium-ion batteries, due to the inconsistent throughput of the positive and negative electrodes to the electrolyte, the negative electrode is liquefied and dark spots, which affects the circulation performance.
By satisfying the specific porosity and thickness formulas (Equation 1 and Equation 2) on the positive and negative electrodes of the lithium-ion battery, the uniform throughput of the electrolyte is ensured. The specific formula is: (τ2*h2-τ1*h1)=k1( ψ1*d1-ψ2*d2) and (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), where k1 is 0.98~1.14, k2 is 0.55~0.63, τ1, τ2, and τ3 are different The positive electrode porosity in SOC, ψ1, ψ2, and ψ3 are the negative electrode porosity in different SOCs, and h1, h2, h3, d1, d2, and d3 are the pole thicknesses in different SOCs.
The circulation performance of lithium-ion batteries is improved, the negative electrode liquid lean and black spot problems are avoided, and the circulation of the battery can be evaluated without long cycles through the detection method, which improves the detection efficiency.
Smart Images

Figure CN119230912A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery preparation, and in particular to a lithium ion battery and a preparation method thereof, and a method for detecting battery cycle performance. Background Art
[0002] As the power source of modern portable electronic devices and electric vehicles, the performance indicators of lithium-ion batteries are particularly important, especially the cyclability (i.e. the ability of the battery to maintain performance after multiple charge and discharge cycles). The basic working principle of lithium-ion batteries is based on the process of lithium ion insertion and deintercalation between the positive and negative electrodes. This process is affected by many factors. For example, the inconsistency of the electrolyte throughput of the positive and negative electrodes during the cyclic charge and discharge process will affect the cyclability of lithium-ion batteries.
[0003] The level of cyclability directly affects the practical application value of lithium-ion batteries. High cyclability means that the battery can withstand more charge and discharge cycles without significantly reducing performance or life, which is crucial to extending the battery's service life and improving the economy and reliability of the system.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a lithium ion battery and a preparation method thereof, and a method for detecting the cycle performance of the battery.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a lithium ion battery, wherein the porosity of the positive electrode and the negative electrode and the thickness of the electrode sheet satisfy the following formula 1 and formula 2:
[0008] Formula 1: (τ2*h2-τ1*h1)=k1(ψ1*d1-ψ2*d2), where k1 is 0.98 to 1.14;
[0009] Formula 2: (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), k2 is 0.55~0.63;
[0010] Wherein, τ1 is the positive electrode porosity at 100% SOC, τ2 is the positive electrode porosity at 26%-28% SOC, τ3 is the positive electrode porosity at 0% SOC, ψ1 is the negative electrode porosity at 100% SOC, ψ2 is the negative electrode porosity at 26%-28% SOC, ψ3 is the negative electrode porosity at 0% SOC, h1 is the positive electrode thickness at 100% SOC, h2 is the positive electrode thickness at 26%-28% SOC, h3 is the positive electrode thickness at 0% SOC, d1 is the negative electrode thickness at 100% SOC, d2 is the negative electrode thickness at 26%-28% SOC, and d3 is the negative electrode thickness at 0% SOC.
[0011] In an optional embodiment, τ2 is the porosity of the positive electrode at 27% SOC, ψ2 is the porosity of the negative electrode at 27% SOC, h2 is the thickness of the positive electrode at 27% SOC, and d2 is the thickness of the negative electrode at 27% SOC.
[0012] In a second aspect, the present invention provides a method for preparing a lithium ion battery, comprising:
[0013] According to the following formula 1 and formula 2, select appropriate positive and negative electrodes to assemble into a battery;
[0014] Formula 1: (τ2*h2-τ1*h1)=k1(ψ1*d1-ψ2*d2), where k1 is 0.98 to 1.14;
[0015] Formula 2: (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), k2 is 0.55~0.63;
[0016] Wherein, τ1 is the pore volume of the positive electrode at 100% SOC, τ2 is the porosity of the positive electrode at 26%-28% SOC, τ3 is the porosity of the positive electrode at 0% SOC, ψ1 is the porosity of the negative electrode at 100% SOC, ψ2 is the porosity of the negative electrode at 26%-28% SOC, ψ3 is the porosity of the negative electrode at 0% SOC, h1 is the thickness of the positive electrode at 100% SOC, h2 is the thickness of the positive electrode at 26%-28% SOC, h3 is the thickness of the positive electrode at 0% SOC, d1 is the thickness of the negative electrode at 100% SOC, d2 is the thickness of the negative electrode at 26%-28% SOC, and d3 is the thickness of the negative electrode at 0% SOC.
[0017] In an optional embodiment, τ2 is the porosity of the positive electrode at 27% SOC, ψ2 is the porosity of the negative electrode at 27% SOC, h2 is the thickness of the positive electrode at 27% SOC, and d2 is the thickness of the negative electrode at 27% SOC.
[0018] In a third aspect, the present invention provides a method for detecting battery cycle performance, comprising:
[0019] Measure the positive electrode porosity, positive electrode thickness, negative electrode porosity, and negative electrode thickness of the battery at 100% SOC; measure the positive electrode porosity, positive electrode thickness, negative electrode porosity, and negative electrode thickness of the battery at 26% to 28% SOC; measure the positive electrode porosity, positive electrode thickness, negative electrode porosity, and negative electrode thickness of the battery at 0% SOC;
[0020] Substitute the measured values into the following formula 1 and formula 2. If the formula is established, the cycle performance is good;
[0021] Formula 1: (τ2*h2-τ1*h1)=k1(ψ1*d1-ψ2*d2), where k1 is 0.98 to 1.14;
[0022] Formula 2: (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), k2 is 0.55~0.63;
[0023] Wherein, τ1 is the positive electrode porosity at 100% SOC, τ2 is the positive electrode porosity at 26%-28% SOC, τ3 is the positive electrode porosity at 0% SOC, ψ1 is the negative electrode porosity at 100% SOC, ψ2 is the negative electrode porosity at 26%-28% SOC, ψ3 is the negative electrode porosity at 0% SOC, h1 is the positive electrode thickness at 100% SOC, h2 is the positive electrode thickness at 26%-28% SOC, h3 is the positive electrode thickness at 0% SOC, d1 is the negative electrode thickness at 100% SOC, d2 is the negative electrode thickness at 26%-28% SOC, and d3 is the negative electrode thickness at 0% SOC.
[0024] In an optional embodiment, τ2 is the porosity of the positive electrode at 27% SOC, ψ2 is the porosity of the negative electrode at 27% SOC, h2 is the thickness of the positive electrode at 27% SOC, and d2 is the thickness of the negative electrode at 27% SOC.
[0025] The present invention has the following beneficial effects:
[0026] The present invention studies the throughput of electrolyte in the positive electrode and negative electrode at 0% SOC, 26% to 28% SOC and 100% SOC, and finds that when the positive electrode porosity, negative electrode porosity, positive electrode thickness and negative electrode thickness meet the above formula 1 and formula 2 provided by the present invention, the problem of black spots appearing in the poor electrolyte of the negative electrode can be solved when the positive and negative electrodes have inconsistent electrolyte throughput during lithium ion battery charge and discharge cycles, that is, the electrolyte spitted out by the positive electrode is much less than the electrolyte required by the negative electrode, thereby improving the cycle performance. Therefore, the lithium battery provided by the present invention has better cycle performance.
[0027] When the formula provided by the present invention is applied to the battery cycle performance test, the battery cycle performance can be tested without long cycle of the battery, and the test efficiency is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0029] Figures 1 to 7 The appearance pictures of the negative electrode sheets obtained after disassembling the batteries after the cycles of Examples 1 to 7 are shown respectively;
[0030] Figures 8 to 10 The following are the appearance pictures of the negative electrode sheets obtained after disassembling the batteries after cycles 1 to 3 of comparative examples, respectively. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0032] The lithium ion battery and the preparation method thereof provided by the embodiments of the present invention are described in detail below.
[0033] The lithium-ion battery provided in the embodiment of the present invention has a positive electrode and a negative electrode, and a pore volume and a pole piece thickness that satisfy the following formula 1 and formula 2:
[0034] Formula 1: (τ2*h2-τ1*h1)=k1(ψ1*d1-ψ2*d2), where k1 is 0.98 to 1.14;
[0035] Formula 2: (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), k2 is 0.55~0.63;
[0036] Wherein, τ1 is the positive electrode porosity at 100% SOC, τ2 is the positive electrode porosity at 26%-28% SOC, τ3 is the positive electrode porosity at 0% SOC, ψ1 is the negative electrode porosity at 100% SOC, ψ2 is the negative electrode porosity at 26%-28% SOC, ψ3 is the negative electrode porosity at 0% SOC, h1 is the positive electrode thickness at 100% SOC, h2 is the positive electrode thickness at 26%-28% SOC, h3 is the positive electrode thickness at 0% SOC, d1 is the negative electrode thickness at 100% SOC, d2 is the negative electrode thickness at 26%-28% SOC, and d3 is the negative electrode thickness at 0% SOC.
[0037] When the battery is in the range of about 0 to 27% SOC, the electrode sheet rebounds greatly. Therefore, taking the vicinity of 27% SOC, for example, 26% to 28% SOC, as a node, by studying the changes in the pore volume of the positive and negative electrodes at 0% SOC, 26% to 28% SOC, and 100% SOC, it is found that when the positive electrode porosity, the negative electrode porosity, and the positive electrode thickness and the negative electrode thickness satisfy the above formula 1 and formula 2 provided by the present invention, the problem of black spots due to the poor electrolyte in the negative electrode caused by the inconsistent electrolyte throughput of the positive and negative electrodes during lithium ion battery charge and discharge cycles can be solved, that is, the electrolyte spitted out by the positive electrode is much less than the electrolyte required by the negative electrode, thereby improving the cycle performance.
[0038] Preferably, τ2 is the porosity of the positive electrode at 27% SOC, ψ2 is the porosity of the negative electrode at 27% SOC, h2 is the thickness of the positive electrode at 27% SOC, and d2 is the thickness of the negative electrode at 27% SOC.
[0039] An embodiment of the present invention provides a method for preparing a lithium ion battery, comprising:
[0040] According to the following formula 1 and formula 2, select appropriate positive and negative electrodes to assemble into a battery;
[0041] Formula 1: (τ2*h2-τ1*h1)=k1(ψ1*d1-ψ2*d2), where k1 is 0.98 to 1.14;
[0042] Formula 2: (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), k2 is 0.55~0.63;
[0043] Wherein, τ1 is the positive electrode porosity at 100% SOC, τ2 is the positive electrode porosity at 26%-28% SOC, τ3 is the positive electrode porosity at 0% SOC, ψ1 is the negative electrode porosity at 100% SOC, ψ2 is the negative electrode porosity at 26%-28% SOC, ψ3 is the negative electrode porosity at 0% SOC, h1 is the positive electrode thickness at 100% SOC, h2 is the positive electrode thickness at 26%-28% SOC, h3 is the positive electrode thickness at 0% SOC, d1 is the negative electrode thickness at 100% SOC, d2 is the negative electrode thickness at 26%-28% SOC, and d3 is the negative electrode thickness at 0% SOC.
[0044] The present invention studies the changes in the pore volume of the positive and negative electrodes at 0% SOC, 26% to 28% SOC and 100% SOC, and finds that when the positive electrode porosity, the negative electrode porosity, the positive electrode thickness and the negative electrode thickness meet the above formula 1 and formula 2 provided by the present invention, the problem of black spots appearing in the poor electrolyte of the negative electrode can be solved when the positive and negative electrodes have inconsistent electrolyte throughput during lithium ion battery charge and discharge cycles, that is, the electrolyte spitted out by the positive electrode is much less than the electrolyte required by the negative electrode, thereby improving the cycle performance. Therefore, according to the requirements of the above formulas 1 and 2, production can obtain lithium ion batteries with good electrochemical performance.
[0045] Preferably, τ2 is the porosity of the positive electrode at 27% SOC, ψ2 is the porosity of the negative electrode at 27% SOC, h2 is the thickness of the positive electrode at 27% SOC, and d2 is the thickness of the negative electrode at 27% SOC.
[0046] Optionally, for a laminated type battery, a positive electrode sheet with a thickness of 143.0 to 153.0 μm (i.e., thickness after rolling) may be selected as the positive electrode, and a negative electrode sheet with a thickness of 115.0 to 125.0 μm (i.e., thickness after rolling) may be selected as the negative electrode;
[0047] The embodiment of the present invention also provides a method for detecting battery cycle performance, comprising:
[0048] Measure the positive electrode porosity, positive electrode thickness, negative electrode porosity, and negative electrode thickness of the battery at 100% SOC; measure the positive electrode porosity, positive electrode thickness, negative electrode porosity, and negative electrode thickness of the battery at 26% to 28% SOC; measure the positive electrode porosity, positive electrode thickness, negative electrode porosity, and negative electrode thickness of the battery at 0% SOC;
[0049] Substitute the measured values into the following formula 1 and formula 2. If the formula is established, the cycle performance is good;
[0050] Formula 1: (τ2*h2-τ1*h1)=k1(ψ1*d1-ψ2*d2), where k1 is 0.98 to 1.14;
[0051] Formula 2: (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), k2 is 0.55~0.63;
[0052] Wherein, τ1 is the positive electrode porosity at 100% SOC, τ2 is the positive electrode porosity at 26%-28% SOC, τ3 is the positive electrode porosity at 0% SOC, ψ1 is the negative electrode porosity at 100% SOC, ψ2 is the negative electrode porosity at 26%-28% SOC, ψ3 is the negative electrode porosity at 0% SOC, h1 is the positive electrode thickness at 100% SOC, h2 is the positive electrode thickness at 26%-28% SOC, h3 is the positive electrode thickness at 0% SOC, d1 is the negative electrode thickness at 100% SOC, d2 is the negative electrode thickness at 26%-28% SOC, and d3 is the negative electrode thickness at 0% SOC.
[0053] The detection method provided by the present invention does not require long-term battery cycling. The battery is disassembled after charging or discharging to measure the pore volume and thickness of the electrode sheet, and then the cyclability of the battery can be detected by calculation, which has the characteristic of high detection efficiency.
[0054] Optionally, τ2 is the porosity of the positive electrode at 27% SOC, ψ2 is the porosity of the negative electrode at 27% SOC, h2 is the thickness of the positive electrode at 27% SOC, and d2 is the thickness of the negative electrode at 27% SOC.
[0055] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0056] Example 1
[0057] This embodiment provides a laminated lithium-ion battery, the active material of the positive electrode is lithium iron phosphate, the thickness is 148.00 μm, and the compaction density is 2.379 mg / cm 3The active material of the negative electrode is graphite, with a thickness of 120 μm and a compaction density of 1.434 mg / cm 3 The diaphragm is PP plus ceramic membrane, the electrolyte formula is: the solute is 1M lithium hexafluorophosphate, and the solvent is 30% vt EC (ethylene carbonate) + 30% vt EMC (ethyl methyl carbonate) + 40% vt DMC (dimethyl carbonate).
[0058] 40 batteries were selected for the experiment and divided into 4 groups, 10 in each group;
[0059] Group 1: The divided batteries were discharged at 0.5C to 0% SOC, the batteries were disassembled, the thickness of the positive electrode and the thickness of the negative electrode were measured, the porosity of the positive electrode and the porosity of the negative electrode were calculated, and the average value of the measurements of 10 batteries was taken.
[0060] The calculation results show that τ3 is 34.80%, ψ3 is 40.85%, h3 is 153.54μm, and d3 is 131.04μm.
[0061] The second group: Take the battery after capacity division, that is, 27% SOC, disassemble the battery, measure the thickness of the positive electrode and the negative electrode, calculate the porosity of the positive electrode and the negative electrode, and take the average value of the measured values of 10 batteries;
[0062] The calculation results show that τ2 is 33.70%, ψ2 is 42.73%, h2 is 151.21μm, and d2 is 135.15μm.
[0063] The third group: Take the batteries after capacity division, charge the batteries at 0.5C to 100% SOC, disassemble the batteries, measure the thickness of the positive electrode and the negative electrode, calculate the porosity of the positive electrode and the negative electrode, and take the average value of the measured values of 10 batteries;
[0064] The calculation results show that τ1 is 31.92%, ψ1 is 44.26%, h1 is 147.61μm, and d1 is 138.68μm.
[0065] Substituting the values calculated from the first to third groups into Formula 1, the formula is valid, and k1 is 1.06; substituting the values calculated from the first to third groups into Formula 2, the formula is valid, and k2 is 0.59, which indicates that the battery of this embodiment has better cyclability.
[0066] Group 4: Verify the cycle performance of the battery. Cycle the battery for 1000 times at 45°C and take the average value of 10 batteries. If the capacity retention rate is greater than 90%, it indicates better cycle performance.
[0067] The experimental results of this group are: capacity retention rate is 90.81%, which shows that the battery of this embodiment has better cycle performance.
[0068] Example 2
[0069] It is basically the same as Example 1, except that the thickness and compaction density of the positive and negative electrodes are different, as shown in Table 1.
[0070] Example 3
[0071] It is basically the same as Example 2, except that the thickness and compaction density of the negative electrode are different, as shown in Table 1.
[0072] Example 4
[0073] It is basically the same as Example 3, except that the thickness and compaction density of the positive electrode are different, as shown in Table 1.
[0074] Example 5
[0075] It is basically the same as Example 4, except that the thickness and compaction density of the negative electrode are different, as shown in Table 1.
[0076] Example 6
[0077] It is basically the same as Example 1, except that the thickness and compaction density of the negative electrode are different, as shown in Table 1.
[0078] Example 7
[0079] It is basically the same as Example 1, except that the thickness and compaction density of the negative electrode are different, as shown in Table 1.
[0080] Comparative Example
[0081] The batteries provided in Comparative Examples 1-3 are basically the same as those in Example 1, except that the thickness and compaction density of the positive and negative electrodes are different. The coating amount of the positive and negative electrode active layers on the current collector is still the same as in Example 1, and the positive electrode is 32.05 g / cm 2 , the negative electrode is 16.43g / cm 2 .
[0082] The performance of each battery of Comparative Examples 1 to 3 was tested using the same experimental method as Example 1. The parameters and test results of Comparative Examples 1 to 3 and Example 1 are recorded in Table 1.
[0083] The performance of each battery of Comparative Examples 1 to 3 was tested using the same experimental method as Example 1. The parameters and test results of Comparative Examples 1 to 3 and Example 1 are recorded in Table 1.
[0084] Table 1 Comparison of parameters and test results of various embodiments and comparative examples
[0085]
[0086]
[0087] Substituting the parameters measured in each comparative example into Formula 1 and Formula 2, it is found that Comparative Examples 1 to 3 do not fully meet the requirements of Formula 1 and Formula 2.
[0088] The capacity retention rates of Example 1 and various comparative examples were compared. The capacity retention rate of Example 1 was significantly higher than those of various comparative examples, which indicates that when the porosity and thickness of the lithium-ion battery satisfy the two formulas provided by the present invention, it has better cycle performance.
[0089] Experimental Example 2
[0090] The batteries of each embodiment and comparative example after 1000 cycles were disassembled and the appearance of the negative electrode sheets was observed as follows: Figures 1 to 10 shown.
[0091] Figures 1 to 7 They correspond to the appearance pictures of the negative electrode sheets after disassembly of Examples 1 to 7, respectively. It can be seen from the pictures that there is almost no black spot problem on the surface of the negative electrode sheet after 1000 cycles, indicating good cycle performance.
[0092] Figures 8 to 10 The corresponding apparent images are of the negative electrode sheets after disassembly of comparative examples 1 to 3. It can be seen from the images that after 1000 cycles, there are obvious black spots on the surface of the negative electrode sheets, indicating that the cycle performance is worse than that of each embodiment.
[0093] In summary, the present invention studies the throughput of electrolyte in the positive and negative electrodes at 0% SOC, 26% to 28% SOC and 100% SOC, and finds that when the positive electrode porosity, negative electrode porosity, positive electrode thickness and negative electrode thickness meet the above formula 1 and formula 2 provided by the present invention, the problem of black spots appearing in the poor electrolyte of the negative electrode can be solved when the positive and negative electrodes have inconsistent electrolyte throughput during lithium ion battery charge and discharge cycles, that is, the electrolyte spitted out by the positive electrode is much less than the electrolyte required by the negative electrode, thereby improving the cycle performance. Therefore, the lithium battery provided by the present invention has better cycle performance.
[0094] When the formula provided by the present invention is applied to the battery cycle performance test, the battery cycle performance can be tested without long cycle of the battery, and the test efficiency is high.
[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: The pore volume of the positive electrode and the negative electrode and the thickness of the electrode sheet satisfy the following formula 1 and formula 2: Formula 1: (τ2*h2-τ1*h1)=k1(ψ1*d1-ψ2*d2), where k1 is 0.98 to 1.14; Formula 2: (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), k2 is 0.55~0.63; Wherein, τ1 is the positive electrode porosity at 100% SOC, τ2 is the positive electrode porosity at 26%-28% SOC, τ3 is the positive electrode porosity at 0% SOC, ψ1 is the negative electrode porosity at 100% SOC, ψ2 is the negative electrode porosity at 26%-28% SOC, ψ3 is the negative electrode porosity at 0% SOC, h1 is the positive electrode thickness at 100% SOC, h2 is the positive electrode thickness at 26%-28% SOC, h3 is the positive electrode thickness at 0% SOC, d1 is the negative electrode thickness at 100% SOC, d2 is the negative electrode thickness at 26%-28% SOC, and d3 is the negative electrode thickness at 0% SOC.
2. The lithium-ion battery according to claim 1, characterized in that τ2 is the positive electrode porosity at 27% SOC, ψ2 is the negative electrode porosity at 27% SOC, h2 is the positive electrode thickness at 27% SOC, and d2 is the negative electrode thickness at 27% SOC.
3. A method for preparing a lithium ion battery, characterized in that: include: According to the following formula 1 and formula 2, select appropriate positive and negative electrodes to assemble into a battery; Formula 1: (τ2*h2-τ1*h1)=k1(ψ1*d1-ψ2*d2), where k1 is 0.98 to 1.14; Formula 2: (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), k2 is 0.55~0.63; Wherein, τ1 is the positive electrode porosity at 100% SOC, τ2 is the positive electrode porosity at 26%-28% SOC, τ3 is the positive electrode porosity at 0% SOC, ψ1 is the negative electrode porosity at 100% SOC, ψ2 is the negative electrode porosity at 26%-28% SOC, ψ3 is the negative electrode porosity at 0% SOC, h1 is the positive electrode thickness at 100% SOC, h2 is the positive electrode thickness at 26%-28% SOC, h3 is the positive electrode thickness at 0% SOC, d1 is the negative electrode thickness at 100% SOC, d2 is the negative electrode thickness at 26%-28% SOC, and d3 is the negative electrode thickness at 0% SOC.
4. The preparation method according to claim 3, characterized in that: τ2 is the positive electrode porosity at 27% SOC, ψ2 is the negative electrode porosity at 27% SOC, h2 is the positive electrode thickness at 27% SOC, and d2 is the negative electrode thickness at 27% SOC.
5. A method for detecting battery cycle performance, characterized in that: include: Measure the positive electrode porosity, positive electrode thickness, negative electrode porosity, and negative electrode thickness of the battery at 100% SOC; measure the positive electrode porosity, positive electrode thickness, negative electrode porosity, and negative electrode thickness of the battery at 26% to 28% SOC; measure the positive electrode porosity, positive electrode thickness, negative electrode porosity, and negative electrode thickness of the battery at 0% SOC; Substitute the measured values into the following formula 1 and formula 2. If the formula is established, the cycle performance is good; Formula 1: (τ2*h2-τ1*h1)=k1(ψ1*d1-ψ2*d2), where k1 is 0.98 to 1.14; Formula 2: (τ3*h3-τ2*h2)=k2(τ2*h2-τ3*h3), k2 is 0.55~0.63; Wherein, τ1 is the positive electrode porosity at 100% SOC, τ2 is the positive electrode porosity at 26%-28% SOC, τ3 is the positive electrode porosity at 0% SOC, ψ1 is the negative electrode porosity at 100% SOC, ψ2 is the negative electrode porosity at 26%-28% SOC, ψ3 is the negative electrode porosity at 0% SOC, h1 is the positive electrode thickness at 100% SOC, h2 is the positive electrode thickness at 26%-28% SOC, h3 is the positive electrode thickness at 0% SOC, d1 is the negative electrode thickness at 100% SOC, d2 is the negative electrode thickness at 26%-28% SOC, and d3 is the negative electrode thickness at 0% SOC.
6. The detection method according to claim 5, characterized in that: τ2 is the positive electrode porosity at 27% SOC, ψ2 is the negative electrode porosity at 27% SOC, h2 is the positive electrode thickness at 27% SOC, and d2 is the negative electrode thickness at 27% SOC.
